2022
DOI: 10.4269/ajtmh.21-0588
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Jaundice: Knowledge and Practices of Healthcare Providers and Trainees in Southwest Nigeria

Abstract: Severe neonatal jaundice (SNNJ) is a leading cause of neonatal morbidity and mortality in low- and middle-income countries (LMICs). Risk mitigation and management modalities for SNNJ have led to a marked reduction in complications in high-income countries but not in LMICs likely in part due to knowledge gaps among healthcare providers. This study, a cross-sectional study conducted in Ogbomosho, Nigeria, aimed to identify SNNJ knowledge and practices among Nigerian healthcare providers/trainees. Healthcare prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…Now decades later after this 1989 recommendation, routine G6PD deficiency screening programs have not been adopted in many regions, even those with a significant burden of G6PD deficiency and SNJ ( 81 ). A recent survey of healthcare providers in Nigeria, one such high risk country, illustrated gaps in knowledge of the common prevalence and need for screening of G6PD deficiency at their local hospital ( 20 ). The combination of routine screening and education of both healthcare workers and parents is needed to reduce the contribution of G6PD deficiency to SNJ globally.…”
Section: Remaining Gapsmentioning
confidence: 99%
See 4 more Smart Citations
“…Now decades later after this 1989 recommendation, routine G6PD deficiency screening programs have not been adopted in many regions, even those with a significant burden of G6PD deficiency and SNJ ( 81 ). A recent survey of healthcare providers in Nigeria, one such high risk country, illustrated gaps in knowledge of the common prevalence and need for screening of G6PD deficiency at their local hospital ( 20 ). The combination of routine screening and education of both healthcare workers and parents is needed to reduce the contribution of G6PD deficiency to SNJ globally.…”
Section: Remaining Gapsmentioning
confidence: 99%
“…Arogbokun et al reported that eucalyptus oil induced a 13.4% increase in hemolysis and methylated spirit showed a 39.7% increase in hemolysis in the zebrafish model ( 94 ). A survey of healthcare workers and trainees in Southwest Nigeria demonstrated that even these medical professionals often recommended hemolytic agents for the umbilical cord (82% recommended methylated spirit) ( 95 ). Other regional practices may delay proper care.…”
Section: Remaining Gapsmentioning
confidence: 99%
See 3 more Smart Citations